Pengembangan Model Fintech-Micro BMT (FIT) - Abdullah Haidar; Nur Hendrasto; Evania Herindar; Fauziah Chairiyati (Perbanas Institute, 2023)
This article's goal is to create a Fintech Micro BMT (FIT) financial technology innovation model for the Islamic microfinance institution Baitul Maal wa Tamwil (BMT) at the APEX/association scale. Being a successful and independent institution (financial self-uffency) as a commercial function and assisting in reducing poverty (poverty alleviation) as a social function are the two fundamental goals of BMT. The goal of fintech micro BMT is to accomplish both objectives. Through the use of descriptive analytic techniques, the research was carried out utilizing qualitative approaches. Primary data from interviews and secondary data from literature reviews make up the utilised data. The basic prototype of the application and its features were analyzed for model innovation using the Business Model Canvas framework. This was followed by a description of the BMT and MSME simple financial reporting accounting systems as well as the credit scoring model. In order to solve the issue of liquidity gaps (mismatch), this study produced a Fintech micro BMT model that maximizes the dualities of commercial BMT functions (increasing market share) and social (ZISWAF). Business management, accounting reporting, as well as a qualified credit rating model, support these two tasks. The triple bottom line purpose of BMT—economic growth, community empowerment, and sustainability—is also embodied by fintech micro BMT. The adoption of Fintech micro BMT is anticipated to assist BMTs in expanding their role in developing the sharia microfinance network, promote cooperation among BMTs in Indonesia, boost the volume of BMT financial transactions, integrate MSME actors as recipients of ZISWAF financing and donors with BMTs, promote market transparency, and lower the risk of information asymmetry in the process of providing financing.